FTO – A Common Genetic Basis for Obesity and Cancer - Lan, Ning; Lu, Ying; Zhang, Yigan; Pu, Shuangshuang; Xi, Huaze; Nie, Xin; Liu, Jing; Yuan, Wenzhen (Frontiers in Genetics, 2020)
In recent years, the prevalence of obesity and cancer are rising, which poses a serious threat to human health，the relationship between the two has also attracted much attention. Here, fat mass and obesity-associated (FTO) gene can be considered as the link, since Genome-wide Association Study (GWAS) identified multiple single nucleotide polymorphism sites (SNPs) of FTO gene, which shows a correlation with obesity and cancer in different populations. Technically, FTO proteins have been proved to participate in adipogenesis and tumorigenesis with post-transcriptional regulation of downstream molecular expression or through target of mammalian target protein of rapamycin (mTOR). Also, FTO inhibitors have also been found to share anti-obesity and anti-cancer effects in vivo. In this review, we comprehensively elaborated on the correlation between obesity or cancer by measuring FTO gene polymorphism, as well as the molecular mechanism involved in these diseases. We emphasized FTO as the common genetic basis of obesity and cancer.